2001
DOI: 10.1053/rmed.2001.1117
|View full text |Cite
|
Sign up to set email alerts
|

Total nitrite/nitrate in expired breath condensate of patients with asthma

Abstract: Production of nitric oxide (NO) is generally increased during inflammatory diseases including asthma. The eventual fate of NO is oxidation to nitrite (NO2) and nitrate (NO3), both of which are end-products of NO metabolism. Hydrogen Peroxide (H2O2) is increased in exhaled breath condensate of asthmatic subjects and may be used as a non-invasive marker of oxidative stress. NO has in some cases been shown to attenuate oxidant-induced lung injury. Total NO2/NO3 concentration and H2O2 levels were measured in expir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
88
1
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(102 citation statements)
references
References 26 publications
10
88
1
3
Order By: Relevance
“…1). These collecting vessels are cooled with wet ice [5], air [24] metal [25] or dry ice to the required temperature. Comparing a custom-made device (Tygon tubing immersed in thawing ice) with a commercially available condenser (Teflon coated laminated metal tube cooled to -20˚C) one study showed that the use of the two devices are interchangeable when measuring MDA, hexanal, heptanal or nonanal [21].…”
Section: Condensing Equipmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). These collecting vessels are cooled with wet ice [5], air [24] metal [25] or dry ice to the required temperature. Comparing a custom-made device (Tygon tubing immersed in thawing ice) with a commercially available condenser (Teflon coated laminated metal tube cooled to -20˚C) one study showed that the use of the two devices are interchangeable when measuring MDA, hexanal, heptanal or nonanal [21].…”
Section: Condensing Equipmentsmentioning
confidence: 99%
“…Protocols, recommendations and potential pitfalls NO 2 -and NO 3 -have been detected in EBC by using spectrophotometric assays (Griess reaction), a fluorimetric method (2,3-diaminonapthalene (DAN) reaction), chemiluminescence assays or ion chromatography followed by conductivity measurement [91][92][93][94][95][96][97][98][99][100][101][102][103][104]. The reported detection limit of the DAN assay is 0.1 mM and that of the Griess reaction is higher [91,92].…”
Section: Level Of Validationmentioning
confidence: 99%
“…The collection of EBC was performed as previously described [15]. Briefly, a heat exchanger unit (RHES, model 6V3; Jaeger, Wuerzburg, Germany) was used to produce cold air of -15uC--18uC at an airflow of w80 L?min -1 .…”
Section: Collection Of Expired Breath Condensatementioning
confidence: 99%
“…after 2 days, 1 week, 2 weeks and 3 weeks of storage (the maximum time between collection and measurement in the frozen samples). All condensate samples were tested for salivary contamination by determination of amylase activity, as previously described [15].…”
Section: Collection Of Expired Breath Condensatementioning
confidence: 99%
“…Nitrite is typically detected through one of several spectrophotometric methods (Griess reaction) involving fluorimetry, chemiluminescence, or ion chromatography [15][16][17][18][19][20][21][22][23][24][25][26][27][28] . The detection limit of fluorimetric methods is 0.1 μM.…”
Section: Introductionmentioning
confidence: 99%